Electrification of Mobility - United Nations Economic Commission for Europe (United Nations, 2025)
The transport sector is a significant contributor to global emissions. In 2019, direct greenhouse gas (GHG) emissions from the transport sector accounted for 23 per cent of global energy-related CO2 emissions (Jaramillo et al. 2022). Most of these emissions come from road transport. The third part of the Sixth Assessment Report of IPCC titled “Climate Change 2022: Mitigation of Climate Change” released in April 2022 suggested that without intervention, CO2 emissions from transport could grow between 16 per cent and 50 per cent by 2050. To meet the Paris Agreement’s objective of limiting global warming to below 2 degrees Celsius compared to pre-industrial levels, it is necessary to achieve rapid decarbonization in all sectors, including transportation. However, the transport sector is currently experiencing a rise in energy demand and GHG emissions, outpacing all other sectors except for industry, and is heavily reliant on fossil fuels. Transitioning to an electric vehicle (EV)-based transport system is an approach that can achieve GHG emissions reductions at the scale necessary to decarbonize transport. This shift would also significantly reduce vehicle pollutant emissions and dependence on fossil fuel imports for transport. The publication explores the transformative impact of electric mobility in the transportation sector, focusing on how electric vehicles (EVs) are reshaping industry dynamics and aligning with sustainable development goals. It discusses the drivers behind EV adoption, including political and environmental factors, and details various policy instruments, such as incentives and regulations, across multiple transport modes. Additionally, it assesses the infrastructure needed for EVs, emphasizing the importance of expanding and standardizing charging solutions.